High proton conductivity through angstrom-porous titania - Yu Ji; Guang-Ping Hao; Yong-Tao Tan; Wenqi Xiong; Yu Liu; Wenzhe Zhou; Dai-Ming Tang; Renzhi Ma; Shengjun Yuan; Takayoshi Sasaki; Marcelo Lozada-Hidalgo; Andre K. Geim; et al. (Nature Communications)
Abstract Two dimensional (2D) crystals have attracted strong interest as a new class of proton-conducting materials that can block atoms, molecules and ions while allowing proton transport through the atomically thin basal planes. Although 2D materials exhibit this perfect selectivity, the reported proton conductivities have been relatively low. Here we show that vacancy-rich titania monolayers are highly permeable to protons while remaining impermeable to helium with proton conductivity exceeding 100 S cm−2 at 200 °C and surpassing targets set by industry roadmaps. The fast and selective proton transport is attributed to an extremely high density of titanium-atom vacancies (one per square nm), which effectively turns titania monolayers into angstrom-scale sieves. Our findings highlight the potential of 2D oxides as membrane materials for hydrogen-based technologies.